2019
DOI: 10.17219/dmp/103911
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the apical extrusion of sodium hypochlorite gel in immature permanent teeth: An in vitro study

Abstract: , which deserves a great appreciation for all academic and financial support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…NaOCl gel has been suggested as an alternative endodontic irrigant because theoretically it has the same antimicrobial action of NaOCl solution, but with less apical extrusion and could thus be safer ( Nesser & Bshara, 2019 ). It is effective in reducing the microbial load, but has been shown to be less effective when compared to NaOCl solution of a lower concentration ( Poggio et al ., 2010 ; Zand et al ., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NaOCl gel has been suggested as an alternative endodontic irrigant because theoretically it has the same antimicrobial action of NaOCl solution, but with less apical extrusion and could thus be safer ( Nesser & Bshara, 2019 ). It is effective in reducing the microbial load, but has been shown to be less effective when compared to NaOCl solution of a lower concentration ( Poggio et al ., 2010 ; Zand et al ., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…NaOCl is a cytotoxic substance ( Salazar-Mercado et al ., 2019 ); overflow during endodontic treatment can cause diverse exacerbations ( Goswami et al ., 2014 ). Thus, NaOCl gel may be safer due to its minor apical extrusion tendency ( Nesser & Bshara, 2019 ). Passive ultrasonic irrigation (PUI) improves RCS disinfection ( Plotino et al ., 2007 ), removing the smear layer and vapor lock during endodontic treatment ( Bueno et al ., 2019 ; Dioguardi et al ., 2019 ), and permits greater penetration of irrigants to the dentinal tubules ( Sáinz-Pardo et al ., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, this solution is highly toxic at high concentrations if it is extruded apically [ 46 ]. The use of of NaOCl gel as an irrigating solution was suggested by some authors to overcome the problem of apical extrusion of its solution form [ 19 , 20 ]. To the best of our knowledge, no dental company produced NaOCl gel as a root canal medicament.…”
Section: Discussionmentioning
confidence: 99%
“…However, when apically extruded, this solution causes significant tissue toxicity [ 18 ]. As a result, using NaOCl in a gel form reduces the risk of apical extrusion and the unfavorable consequences of the solution form [ 19 , 20 ]. Sodium hypochlorite (NaOCl) gel is currently available under the name of bleaching pen (Clorox Bleach Pen, USA) to clean precisely the dirty white clothes.…”
Section: Introductionmentioning
confidence: 99%
“…Zand et al suggested that the adverse effects of sodium hypochlorite solution can be prevented by using NaOCl gel [9]. In addition, NaOCl solution cannot be used as an irrigant in immature teeth, thus gel form was a safe alternative for immature teeth irrigation with an open apex up to 2.5 mm [16]. Furthermore, gel form demonstrated better behavior than solution form on deciduous molars dentin [17].…”
mentioning
confidence: 99%